Preparation and characterization of boron-based bioglass by sol−gel process - Furlan, Roberto Gustavo; Correr, Wagner Raphael; Russi, Ana Flavia Costa; da Costa Iemma, Mônica Rosas; Trovatti, Eliane; Pecoraro, Édison [UNESP] (Springer Nature, 2018)
45S5 bioglass has been widely studied in the last few decades because of its bioactivity and promising applications in the biomedical field. Boron, even few studied, represents a potential element to improve the properties of the 45S5 bioglass derivatives. The bioglasses are conventionally prepared by heat treatment of oxides and silicon. Here, the sol−gel method is proposed for the preparation of the boron-based 45S5 bioglass (45S5B) and the classical 45S5 bioglass (45S5), using water-soluble salts as raw materials. The bioglasses were characterized by FTIR, XRD, and SEM, indicating the success of the sol−gel method for preparation of the samples. The bioglasses were also tested in vitro for bioactivity in biological conditions and cytotoxicity against eukaryotic cells. The bioactivity of 45S5B was similar to the bioactivity of 45S5 bioglass, indicated by the deposition of hydroxyapatite crystals at the surface of the pristine bioglasses. The results of cytotoxicity tests revealed that the IC50 of 45S5B (IC50 = 7.56 mg mL−1) was similar to the IC50 of 45S5 (IC50 = 8.15 mg mL−1), indicating its safety for application in the biomedical field. [Figure not available: see fulltext.].
Keywords: 45S5; Bioglass; Boron; Cytotoxicity; in vitro; OSTEO-1 cells